Loneliness as a Lethal Risk Factor: A Five-Year Prospective Survival Analysis of All-Cause Mortality Among Elderly Residents in Indonesian Vertical Public Housing - Dedi Sucipto; Brenda Jaleel; Aline Hafidzah; Oliva Azalia Putri (Scientia Psychiatrica, 2025)
Introduction: Rapid urbanization in Indonesia has necessitated a shift from horizontal settlements (kampung) to vertical public housing (Rusunawa). While providing shelter, these environments may exacerbate "crowded isolation”. This study investigates the synergistic impact of loneliness, depression, and vertical living constraints on all-cause mortality among the elderly. Methods: We conducted a multi-center, prospective cohort study (2018–2023) involving 1,450 elderly residents (> 60 years) in Jakarta and Surabaya. Loneliness was assessed annually using the UCLA Loneliness Scale, and depression via the GDS-15. The primary environmental exposure was "vertical constraint," defined as living above the 3rd floor (Floors 4–12). We utilized Kaplan-Meier survival curves and Multivariable Cox Proportional Hazards models with time-dependent covariates to estimate Hazard Ratios (HR), adjusting for sociodemographic factors and a composite Socioeconomic Status (SES) index. Results: Of 1,398 baseline participants, 218 deaths occurred over 6,890 person-years (15.6% mortality). Severe loneliness was an independent predictor of mortality (Adjusted HR: 1.89; 95% CI: 1.42–2.51). A significant interaction was observed between loneliness and vertical constraint (p=0.003). While residents on higher floors had lower baseline mortality due to selection bias (the "healthy resident effect"), loneliness in this subgroup amplified mortality risk substantially (Interaction HR: 1.76; 95% CI: 1.21–2.55), effectively negating their physical survival advantage. Conclusion: Loneliness is a potent predictor of mortality in Indonesian vertical slums, with lethality accelerated by the physical entrapment of high-floor living. Structural interventions are urgently required to mitigate this "vertical isolation."